2013
DOI: 10.1051/0004-6361/201321047
|View full text |Cite
|
Sign up to set email alerts
|

Size and disk-like shape of the broad-line region of ESO 399-IG20

Abstract: We present photometric reverberation mapping of the narrow-line Seyfert 1 galaxy ESO 399-IG20 performed with the robotic 15 cm telescope VYSOS-6 at the Cerro Armazones Observatory. Through the combination of broad-and narrow-band filters we determine the size of the broad-line emitting region (BLR) by measuring the time delay between the variability of the continuum and the Hα emission line. We use the flux variation gradient method to separate the host galaxy contribution from that of the active galactic nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…There were observations on 27 days, from which 24 had exposures in B, 19 in R, and 7 in the V filter. Data reduction and processing of the OCA data was performed in the same manner as reported in Pozo Nuñez et al (2013).…”
Section: A7 Ocamentioning
confidence: 99%
“…There were observations on 27 days, from which 24 had exposures in B, 19 in R, and 7 in the V filter. Data reduction and processing of the OCA data was performed in the same manner as reported in Pozo Nuñez et al (2013).…”
Section: A7 Ocamentioning
confidence: 99%
“…Disc-shaped BLRs are popular in the literature (e.g. Decarli et al 2008;Gaskell & Goosmann 2013;Begelman & Silk 2016) and are commonly invoked to explain reverberation mapping results (Pozo Nuñez et al 2013;Pancoast et al 2014a,b;Goad & Korista 2014). Furthermore, R11 suggested that the broad emission lines form in a disc and trace the disc emission in terms of their anisotropy.…”
Section: Line Anisotropymentioning
confidence: 99%
“…All these CCF methods share a key assumption that the light curve containing contribution from the broad-line emission must be dominated by it, otherwise the peak at the position of a non-zero lag would be overwhelmed by the auto-correlation peak of the continuum at zero lags. Thus generally CCF-like methods only apply to spectroscopic reverberation mapping, sometimes also to broadband+narrowband photometric RM (e.g., Haas et al 2011;Pozo Nuñez et al 2013;Jiang et al 2016), in which, however, the contribution from the continuum to the narrow band light curve must be subtracted carefully. There are also some works applying CCF-like methods directly to broadband photometric data (e.g., Chelouche et al 2012), but due to the fact that the typical relative contribution of a broad emission line to the whole broadband is of the order of a few percent, this method cannot be expected to perform well on most of the quasars whose variability information comes only from their broadband photometric data.…”
Section: Introductionmentioning
confidence: 99%